Foreign aid and the fragile consensus on state fragility - Jörg Faust; Jörn Grävingholt; Sebastian Ziaja (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Most actors in the field of foreign aid agree with the call for coordinated engagement in fragile states in order to more effectively counter the consequences and origins of state failure. However, despite such demands, governments from OECD countries as well as multilateral agencies that are engaged in fragile states often continue to act in an uncoordinated manner and fail to reach higher levels of harmonisation. Why is effective coordination so hard to achieve? This article argues that three major challenges explain the persistent problems of donor harmonisation in fragile states: (1) the cognitive challenge of explaining the origins of state fragility and deducing effective instruments and interventions; (2) the political challenge of reconciling divergent political motives for engagement; as well as (3) the challenge related to the organisational logic of competing aid agencies.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten